Complications Leading to Keratoplasty among Contact Lens Users and LASIK Patients: A 10-Year Cross-Sectional Analysis - Sloan W. Rush; Blaze Bulla; Ryan B. Rush (Journal of Ophthalmology)
Purpose. To determine the incidence and outcomes in patients who underwent penetrating keratoplasty (PK) resulting from complications related to contact lens (CL) use and laser in situ keratomileusis (LASIK) in a metropolitan area of the United States. Methods. Population data was obtained from the United States Census Bureau and the Centers for Disease Control. A retrospective, cross-sectional chart review was performed on all patients who underwent keratoplasty in a specific metropolitan geographic area over a ten-year period. The main outcome was best-corrected visual acuity (BCVA) at 2 years in patients who underwent PK secondary to complications related to CL use and LASIK. The secondary outcome was the relative risk of undergoing PK secondary to a complication related to CL use versus LASIK. Results. The study’s geographic area had 46,545 CL users in one or both eyes during any given year and 10,285 patients who underwent LASIK in one or both eyes during the study interval. There were 24 CL users (0.52 per 1,000) and 3 post-LASIK patients (0.29 per 1,000) who underwent PK secondary to complications during the study interval (OR 1.77 [0.53–5.87, 95% CI]; p=0.35). BCVA at 2 years was 1.45 [1.0–1.90] logMAR (20/564 Snellen) in the CL using cohort and 0.07 [−1.19–1.33] logMAR (20/23 Snellen) in post-LASIK cohort following PK (p=0.04). Conclusions. Patients who underwent PK secondary to complications related to CL use had worse visual outcomes at 2 years compared to those related to LASIK. Complications leading to PK were rare in both cohorts, but the incidence of undergoing PK secondary to CL use trended higher than LASIK.